Chillers: The Nearly Ghost Baby - Huddy, Delia (Penguin Group, 1997)
Beach House seems like an ideal holiday spot for Lisa and her family.But they learn about an old tragedy which still haunts the house.
Keywords: Horror & Ghost Stories; Juvenile Fiction